Improvement of soybean grain nutritional quality under foliar inoculation with Azospirillum brasilense strain Az39 - Puente, Mariana Laura; Zawoznik, Myriam; Lopez De Sabando, Marcelo; Perez, Gonzalo; Gualpa, Jose Luis; Carletti, Susana M.; Cassán, Fabricio Dario (2018)
Legumes depend on biological nitrogen fixation through symbiosis with rhizobia to meet their nitrogen requirements. Certain plant growth promoting rizobacteria such as Azospirillum may cooperate in the establishment and maintenance of effective legume-rhizobia symbiosis. The aim of this work was to assess if foliar inoculation of soybean with Azospirillum brasilense Az39 has advantages over inoculation with this bacterium at sowing in combination with Bradyrhizobium japonicum E109 inoculation. To test this, glasshouse and field experiments were carried out. Higher shoot biomass was observed at V6 and R2 stages under foliar inoculation of A. brasilense Az39 as compared to coinoculation at sowing. Additionally, increased root dry biomass and higher nodule number and nodule fresh weight per plant were found at V6. Leghemoglobin levels in nodules were significantly greater in foliar-inoculated plants at both stages (V6 and R2) as compared with seed-inoculated plants. In line with these positive effects of foliar inoculation with A. brasilense Az39 on soybean growth and nodulation, grains harvested from foliar-inoculated plants had higher nitrogen and protein contents than those harvested from plants coinoculated at sowing. This was corroborated for two soybean varieties cultivated at two different locations. Our findings may open new insights into soybean agricultural technology.